2005
DOI: 10.1016/j.ssi.2005.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Ionic conductivity of stabilized zirconia networks in composite SOFC electrodes

Abstract: The effective oxygen conductivities in the zirconia networks of porous LSM- 0.89 , respectively] were evaluated by an AC impedance technique using specimens in which LSM was removed by hydrochloric acid leaching. The oxygen conductivities of porous YSZ and SYSZ alone followed a Koh-Fortini relationship. LSM-containing zirconia network conductivities were additionally decreased by the presence of the LSM, presumably by increased grain boundary resistances. Constriction resistances were estimated to have a min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 7 publications
(2 reference statements)
1
61
0
2
Order By: Relevance
“…and co-workers, [10] or to the creation of new oxygen reduction sites and additional triple phase boundaries with the cobalt spinel particles. The performance improvement and the reduction in non-ohmic resistance by cobalt infiltration for these cathodesupported cells was consistent with most of the results reported for Ni-SYSZ anode supported SYSZ cells [5], in which cobalt was infiltrated into a thin-film LSM-SYSZ cathode.…”
Section: Electrochemical Performancesupporting
confidence: 90%
See 2 more Smart Citations
“…and co-workers, [10] or to the creation of new oxygen reduction sites and additional triple phase boundaries with the cobalt spinel particles. The performance improvement and the reduction in non-ohmic resistance by cobalt infiltration for these cathodesupported cells was consistent with most of the results reported for Ni-SYSZ anode supported SYSZ cells [5], in which cobalt was infiltrated into a thin-film LSM-SYSZ cathode.…”
Section: Electrochemical Performancesupporting
confidence: 90%
“…6. The authors previously reported [5] that Co 3 O 4 nano-particles with an average size of 25 nm were found by TEM in the pores of infiltrated LSM-SYSZ composites heated up to an operational temperature of 650˚C. The improvement by cobalt infiltration might be attributed to enhancement of surface exchange processes on the LSM itself, such as discussed by Kilner, Steele.…”
Section: Electrochemical Performancementioning
confidence: 93%
See 1 more Smart Citation
“…4 Because oxygen ion conduction is poor in LSM, [5][6][7] it is generally believed that the vicinity of three-phase boundaries ͑TPBs͒ of LSM cathode constitutes the active site for ORR. [8][9][10][11] Therefore, numerous studies have employed porous, high-surface-area electrodes with nanometer-scale LSM particle sizes [12][13][14] or composite LSM-YSZ 3,15,16 to enhance overall TPB length and thus lower ORR resistance and overpotential. However, it is not apparent how LSM particle sizes alter the rate-limiting reaction of ORR and the contributions of the TPB and bulk pathway 6,17,18 as a function of temperature, which limits the efficiency optimization of porous electrodes for intermediate temperature operation.…”
mentioning
confidence: 99%
“…Após essa etapa, a pastilha foi novamente pesada e a diferença de peso atribuída à água retida nos poros. Métodos mais complexos para a medida de porosidade são referidos na literatura, como massa específica do material [19], condutividade iônica [20], análise digital da estrutura [21], e outros métodos especiais [22,23]. Entretanto, os resultados dessas técnicas mais elaboradas não mostram nenhuma vantagem sobre o método da absorção de água ou solvente.…”
Section: Preparação Da Célula Unitáriaunclassified